Posture Analysis of Fish Transporting Workers at the Sadeng Beach Fish Auction Place - Choirul Bariyah; Effendi Muhamad (Jurnal Ilmiah Dinamika Rekayasa, 2024)
At the Fish Auction Place (TPI) of Sadeng Beach, Gunung Kidul, fish are manually transported using wooden bearers and pieces of plastic drums used as fish containers. The weight of the transported fish ranged from 90 - 110 kg for each transfer. The fish transport was carried out on the shoulders of two workers of different heights and ages. During fish transporting, the workers had awkward working postures. The worker's posture was characterized by flexion, inclination, and torsion. The Nordic Body Map (NBM) survey revealed reports of stiffness and pain in the shoulders, lower back, and knees. This study aims to evaluate the potential risk of injury in the process of fish transporting. The evaluation used the Rapid Entire Body Assessment (REBA) technique. The findings indicated that both workers'activities fell into the high-risk category, with a REBA score of 14.00, remarked with a very high-risk category. Immediate activity improvement is necessary for safety from injury risks.